2023
DOI: 10.1186/s12889-023-15100-4
|View full text |Cite
|
Sign up to set email alerts
|

Plant and animal protein intake and its association with depression, anxiety, and stress among Iranian women

Abstract: Background Mental disorders are conditions that affect the usual function of the brain, causing a huge burden on societies. The causes are often unclear, but previous research has pointed out, as is the case with many other diseases, that nutrition could have a major role in it. Amino acids, the building blocks of proteins, are the main precursor of neurotransmitters (the chemical messengers in the brain) malfunction of which is heavily associated with a wide range of brain disorders. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
5
0
1
Order By: Relevance
“…In contrast, it has been shown that a high-fiber diet improves glucose homeostasis, serum lipid profiles, inflammatory chemokines, and depression and anxiety symptoms in patients with T2DM [95]. Evaluating the effects of different sources of protein on the mental well-being of women showed that women who consumed more animal protein had a higher chance of showing symptoms of depression (OR: 2.63; 95% CI: 1.45, 4.71; p = 0.001), stress (OR: 3.66; 95% CI: 2.06, 6.50; p < 0.001), and anxiety (OR: 1.83; 95% CI: 1.04, 3.22; p = 0.03), while no significant association was found between plant protein and these mental disorders [96]. Polyunsaturated fats have also been found to be effective in reducing symptoms of depression and anxiety.…”
Section: Exploring the Role Of Nutrition In Preventing And Managing D...mentioning
confidence: 89%
“…In contrast, it has been shown that a high-fiber diet improves glucose homeostasis, serum lipid profiles, inflammatory chemokines, and depression and anxiety symptoms in patients with T2DM [95]. Evaluating the effects of different sources of protein on the mental well-being of women showed that women who consumed more animal protein had a higher chance of showing symptoms of depression (OR: 2.63; 95% CI: 1.45, 4.71; p = 0.001), stress (OR: 3.66; 95% CI: 2.06, 6.50; p < 0.001), and anxiety (OR: 1.83; 95% CI: 1.04, 3.22; p = 0.03), while no significant association was found between plant protein and these mental disorders [96]. Polyunsaturated fats have also been found to be effective in reducing symptoms of depression and anxiety.…”
Section: Exploring the Role Of Nutrition In Preventing And Managing D...mentioning
confidence: 89%
“…These potential mechanisms may mediate the relationship between fish intake and BD risk. Other studies, including a Japanese study linking plant protein with reduced depression symptoms and observational research linking high animal protein intake in women with a higher risk of mental illnesses, support these findings (64,65). A meta-analysis that included eight observational studies showed that meat consumption may be associated with a slightly higher risk of depression (66).…”
Section: Discussionmentioning
confidence: 91%
“…Studies have indicated that individuals with mental disorders tend to have a diminished intake of vegetables, fruits, whole grains, and fiber in their dietary habits. [42,43]. Consequently, a low-quality diet consumed during episodes of depressive symptoms may increase the risk of developing diabetes.…”
Section: The Role Of Physical Activity On Depression In Adults With D...mentioning
confidence: 99%